2021
DOI: 10.1016/j.radcr.2021.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Quadrilateral space region inflammation and other incidental findings on shoulder MRI following recent COVID-19 vaccination: Three case reports

Abstract: We present 3 cases reporting the normal appearance of the post COVID-19 vaccination on shoulder MRI exams. All three patients were imaged 1-5 days post-vaccination for unrelated MSK shoulder symptoms, and none reported any symptoms besides mild shoulder discomfort for a day or two following vaccine administration. All three patients demonstrated characteristic deltoid edema, quadrilateral space region edema and axillary nodal prominence. Vessel prominence with T2 and T1 increased signal draining to the approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The number of visible axillary lymph nodes in both areas was significantly higher in the vaccine group (median [range], 15 nodes ) than in the metastasis group (7 nodes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]) (Table 2). The median and range of the short lymphadenopathy diameter in the ventral side of the axilla were significantly larger in the metastasis group (8.0 mm [5.5-22.5]) than in the vaccine group (6.4 mm [5.2-10.0]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of visible axillary lymph nodes in both areas was significantly higher in the vaccine group (median [range], 15 nodes ) than in the metastasis group (7 nodes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]) (Table 2). The median and range of the short lymphadenopathy diameter in the ventral side of the axilla were significantly larger in the metastasis group (8.0 mm [5.5-22.5]) than in the vaccine group (6.4 mm [5.2-10.0]).…”
Section: Resultsmentioning
confidence: 99%
“…Level I lymph nodes are divided into three groups: the pectoral (anterior), subscapular (posterior), and humeral (lateral) groups [ 10 , 14 , 15 ]. There are no previous reports on the lymphatic pathway from the deltoid muscle; therefore, details regarding this pathway are not yet known [ 16 , 17 ]. Breast lymphatic drainage predominantly occurs into the pectoral (anterior) group of level I lymph nodes, while upper extremity lymphatic drainage predominantly occurs into the humeral (lateral) group of these lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…It is established that vaccine administration leads to a local inflammatory response in a certain number of cases, involving injection site muscles and the lymphnodes afferent to the injection site. Therefore, this is responsible of the increased 18 FDG uptake of axillary lymphnodes on the PET-CT [9] .…”
Section: Discussionmentioning
confidence: 99%
“… Six weeks and three months after discharge, inspection showed that the pain disappeared, the shoulder joint effusion subsided, and the shoulder joint range of motion was normal. 2 1 21 Male Pfizer-BioNTech COVID-19 vaccination First Fifteen hours after receiving vaccination Not record Swelling sensation in the armpit, mild swelling in the neck lymph nodes, and mild tenderness in the injection area. Not record MRI showed secondary deltoid edema and mild inflammation in the axillary area.…”
Section: Methodsmentioning
confidence: 99%